HUBUNGAN ANTARA KARAKTERISTIK PEKERJA DAN PENGAWASAN TERHADAP PERILAKU TIDAK AMAN PADA TEKNISI PERAWATAN HANGAR PESAWAT PT X - Alfandira Rossa Ristantya; Bina Kurniawan; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2022)
Unsafe behavior is a failure to apply work rules and procedures, resulting in work accidents. Work accidents in the aviation are not spared from work accidents that can be experienced by technicians when carrying out aircraft maintenance and repairs. The development of the aviation industry in Indonesia is not proportional to the availability of the number of flight technician workers, resulting in an increase of work-related accidents experienced by flight technicians. Therefore, an approach is needed to determine the behavior of technicians that cause work accidents. This study aims to analyze the relationship between worker characteristics (knowledge, attitude, and working period) and supervision with unsafe behavior in PT X hangar maintenance technicians. This research is quantitative research with cross-sectional study design. The sample in this study were mechanic technicians shift I totaling 120 people who were obtained by random sampling. Data in this study were collected by using a questionnaire and the results were tested using the chi square test. The results of this study indicate that there is a correlation between attitude (p-value: 0,000) on unsafe behavior in PT X aircraft maintenance technicians. Meanwhile, there was no correlation between knowledge (p-value: 0.388), work period (p-value: 0.694), supervision (p-value: 0.305) and unsafe behavior. From the results obtained, hopefully management can add topics to safety briefings and improve the safety information media.